Consumer-Citizens of China: The role of foreign brands in the imagined future China - Tian, Kelly; Dong, Lily (Routledge Contemporary China Series, 2010)
A PDF version of this book is available for free in open access via www.tandfebooks.com as well as the OAPEN Library platform, www.oapen.org. It has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license and is part of the OAPEN-UK research project. This book presents a comprehensive examination of Chinese consumer behaviour and challenges the previously dichotomous interpretation of the consumption of Western and non-Western brands in China. The dominant position is that Chinese consumers are driven by a desire to imitate the lifestyles of Westerners and thereby advance their social standing locally. The alternative is that consumers reject Western brands as a symbolic gesture of loyalty to their nation-state. Drawing from survey responses and in depth interviews with Chinese consumers in both rural and urban areas, Kelly Tian and Lily Dong find that consumers situate Western brands within select historical moments. This embellishment attaches historical meanings to Western brands in ways that render them useful in asserting preferred visions of the future China. By highlighting how Western brands are used in contests for national identity, Consumer-Citizens of China challenges the notion of the "patriot’s paradox" and answers scholars’ questions as to whether Chinese nationalists today allow for a Sino-Western space where the Chinese can love China without hating the West. Consumer-Citizens of China will be of interest to students and scholars of business studies, Chinese and Asian Studies and Political Science. Kelly Tian is Professor of Marketing and holds the Anderson Chair of Business at New Mexico State University. Lily Dong is Associate Professor of Marketing at the University of Alaska at Fairbanks.